2018
DOI: 10.1891/0886-6708.v33.i3.547
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Psychological Distress Among Young Couples: The Role of the Pattern of Violence

Abstract: The objective of this study was to assess whether the psychological distress of young men and women involved in intimate partner violence (IPV) is predicted by their reported role in the pattern of violence. Dyadic structural equation modeling (SEM) analyses were performed on a sample of 205 young couples, controlling for income, cohabitation, children, and the length of the relationship. Findings revealed that the most common reported pattern of IPV was mutual in nature. Reported bidirectional violence within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Researchers and clinicians have examined how individual posttraumatic stress affects spouses/partners and relationship functioning, though this research has mostly been limited to examinations of role disruption, parenting problems, poorer family adjustment, difficulties with intimacy, lower relationship cohesion and satisfaction, greater conflict, anger, and violence (Goff & Smith, 2005). More recent research has found that bidirectional violence within couples is related to distress of both partners (Sader et al, 2018). Given possible effects of both partners' PTSD on their spouses' psychology, distress, and behaviors, as well as data suggesting that women's IPV may primarily represent a response to men's behavior, there is a need to study the possible effects of men's PTSD-related cognitive bias on women's IPV.…”
Section: Gender Social Information Processing and Intimate Partner Vi...mentioning
confidence: 99%
“…Researchers and clinicians have examined how individual posttraumatic stress affects spouses/partners and relationship functioning, though this research has mostly been limited to examinations of role disruption, parenting problems, poorer family adjustment, difficulties with intimacy, lower relationship cohesion and satisfaction, greater conflict, anger, and violence (Goff & Smith, 2005). More recent research has found that bidirectional violence within couples is related to distress of both partners (Sader et al, 2018). Given possible effects of both partners' PTSD on their spouses' psychology, distress, and behaviors, as well as data suggesting that women's IPV may primarily represent a response to men's behavior, there is a need to study the possible effects of men's PTSD-related cognitive bias on women's IPV.…”
Section: Gender Social Information Processing and Intimate Partner Vi...mentioning
confidence: 99%
“…If adolescents’ decision-making, coping, communication, and assertive skills are poor, they may become addicted to cigarettes and alcohol because of social benefits. People with low social competence and skills show the worst prognosis and the highest rate of substance use 2…”
Section: Factors Of the Tendency To Use Addictive Substancesmentioning
confidence: 99%
“…Statistics show that about 16% of addicts in Iran are under 19 years old and 28% between the ages of 20 and 24 become addicted. According to the Welfare Organization, 4% of self-reported addicts under the age of 15 and 24.4% between the ages of 15 and 19 and a total of 56.3 under the age of 24 start using drugs 1,2. Adolescents are more susceptible to age-specific causes, such as creating opportunities to challenge self-centered feelings, displaying a sense of independence, gaining access to peer groups, and relieving developmental stress, which can lead to problems such as delinquency and widespread use.…”
mentioning
confidence: 99%
“…Today, we see a lot of young couples who prescribe and recommend drugs to each other, and if he sees that his friend cannot have sex, he encourages him to use drugs. 2,[7][8][9] People initially use drugs for shortterm pleasure and have a reason to use them, but eventually become addicted to drugs, and it is too late, and the person can no longer get rid of this substance, so he will suffer a lot of harm to that person. The common misconception among teenagers and young adults is that consuming crystal improves the quality of sex, while this belief is completely false.…”
mentioning
confidence: 99%
“…Because this feeling is not real and is caused by the consumption of a foreign substance such as crystal (methamphetamine), and mental imbalance can be observed and recognized in this group of people. [1][2][3] When a person experiences the use of these substances in sex, he gradually thinks that he cannot have a relationship at all without consuming crystal, and this relationship will not be enjoyable, while this feeling is wrong, and this makes the person dependent on substance use, and one can no longer have a healthy relationship without substance use. [4][5][6] The most worrying thing is when a couple sees the positive effect of that false substance and even introduces it to another person.…”
mentioning
confidence: 99%